2015
DOI: 10.1002/pat.3526
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐mechanical sensors based on conductive hybrid nanocomposites

Abstract: This work demonstrates the development of electro-mechanical sensors using a generic methodology based on elastomeric conductive nanocomposites. A fast and facile fabrication route is used to construct a unique architecture based on polymerization of aniline in the presence of dissolved styrene-isoprene-styrene (SIS) tri-block copolymer and carbon nanotubes (CNT), followed by a precipitation-filtration step. The resulting nanocomposites form a segregated network of conductive pathways containing CNT. The perco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The organic solvent can be removed by vacuum degassing or heating [7d,10a,11c,65,66] . Another method is to pour the mixed liquid into methanol and precipitate to obtain composites [10b,67] . Compared with direct mixing, composites made by solution mixing generally have better filler dispersion and a wider range of filler content.…”
Section: Fabricationmentioning
confidence: 99%
“…The organic solvent can be removed by vacuum degassing or heating [7d,10a,11c,65,66] . Another method is to pour the mixed liquid into methanol and precipitate to obtain composites [10b,67] . Compared with direct mixing, composites made by solution mixing generally have better filler dispersion and a wider range of filler content.…”
Section: Fabricationmentioning
confidence: 99%
“…A four-point probe technique showed that the composite displayed high conductivity (~4 S cm −1 ) by forming continuous three-dimensional CNT/PANI networks [31]. They also tested the effectiveness of a three-dimensional segregated conductive SIS/CNT/PANI nanocomposite network as an electro-mechanical strain sensor for two different elastomers: SIS-14% and SIS-22% [32]. The mechanical properties (Young's modulus and stress at break) were much higher with SIS-22% than with SIS-14%.…”
Section: Grafting-from Through Inverse Emulsion Polymerizationmentioning
confidence: 99%
“…Carbon nanotubes (CNT) are an ideal reinforcement for polymers due to their high aspect ratio and exceptional mechanical, electrical and thermal properties. [1][2][3][4][5] The polymer/CNT nanocomposites show many benefits over conventional composites such as good electrical conductivity at very low filler fraction, high thermal and mechanical performances with light weight and low cost as well as little viscosity for easy processing. The improved electrical properties of polymer/CNT nanocomposites motivate the utilization of these materials in various areas such as electronics, sensors, biomedical devices, aerospace and automotive.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNT) are an ideal reinforcement for polymers due to their high aspect ratio and exceptional mechanical, electrical and thermal properties . The polymer/CNT nanocomposites show many benefits over conventional composites such as good electrical conductivity at very low filler fraction, high thermal and mechanical performances with light weight and low cost as well as little viscosity for easy processing.…”
Section: Introductionmentioning
confidence: 99%